Pengaruh Dana Pihak Ketiga dan SWBI terhadap Return Pada Bank Syariah Studi Kasus Pada PT Bank Mandiri Syariah, Tbk Periode Maret 2009 s.d. Juni 2013 - Muhammad Luthfi (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2013)
Islamic banking in Indonesia has experienced rapid growth in which the principles of sharia or the results have proved its resilience against t he economic crisis. This study aims to determine th e effect of third-party funds and SWBI to return (inc ome mudharabah and Musyarakah). The results of this study indicate that the third-party funds have a significant positive effect on the return to the significance of the results t count 0,019 and 2,246 SWBI have a significant negative e ffect on the results of t count return of -2.789 to 0.008 sebesar significance. Ta ken together SWBIs deposits and have an influence on the return. Keywords; Third Party Funds, Return and SWBI